A facile and general approach for the direct fabrication of N-rGO–metal(metal oxides)–Pt composites as electrocatalyst for oxygen reduction reactions. Issue 48 (31st July 2018) - Chen, Xiaohong; Ning, Zhaoyang; Zhou, Zongshang; Liu, Xundao; Lei, Jianlong; Pei, Supeng; Zhang, Yongming
Abstract : We developed a facile, yet general approach to prepare N-rGO–M(MO)–Pt (M = Co, Fe and Mn) composites, which showed excellent electrocatalytic activity for the ORR in alkaline electrolytes. Abstract : Nitrogen-doped reduced graphene oxide–metal(metal oxides) nanoparticle (N-rGO–M(MO) NPs, M = Fe, MO: M = Co, Mn) composites were prepared through a facile and general method at high temperature (800 °C). M(MO) were well-dispersed and tightly anchored on graphene sheets, which were doped with nitrogen simultaneously and further loaded with Pt nanoparticles. Those results showed a more positive onset potential, higher cathodic density, and higher electron transfer number for the ORR in alkaline media. Furthermore, N-rGO–metal(metal oxides)–Pt (N-rGO–M(MO)–Pt) nanoparticles show better durability than the commercial Pt/C catalyst, and can be used as promising potential materials in practical applications.